Ascophyllum nodosum Extract and Glycine Betaine Preharvest Application in Grapevine: Enhancement of Berry Quality, Phytochemical Content and Antioxidant Properties - Eliana Monteiro; Miguel Baltazar; Sandra Pereira; Sofia Correia; Helena Ferreira; Fernando Alves; Isabel Cortez; Isaura Castro; Berta Gonçalves (MDPI AG, 2023)
The Douro Demarcated Region (DDR) has peculiar edaphoclimatic characteristics that provide a suitable terroir for premium wine production. As climate change effects continue to emerge, ensuring productivity and quality becomes increasingly important for viticulturists, as those directly determine their profits. Cultural approaches, such as the use of biostimulants, are actively being developed to mitigate abiotic stress. The main objective of this work was to assess the effect of foliar sprays of a seaweed (Ascophyllum nodosum)-based extract (ANE) and glycine betaine (GB) on grape berry quality, bioactive compounds, and antioxidant activity. A trial was installed in a commercial vineyard (cv. 'Touriga Franca') in the Douro Superior (Upper Douro) sub-region of the Douro Demarcated Region. In 2020 and 2021, three foliar sprayings were performed during the growing season, namely at pea size, bunch closure, and veraison. There was a positive effect of both biostimulants (ANE and GB) on the physiological and biochemical performance of cv. 'Touriga Franca' exposed to summer stress. In general, the GB 0.2% spraying was the most promising treatment for this grape cultivar, as it increased berry quality, the concentration of bioactive compounds (total phenolics, flavonoids, and ortho-diphenols), and the antioxidant activity. These results revealed the efficacy of biostimulant sprayings as a sustainable viticultural practice, improving berry quality under summer stress conditions.